Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s12933-018-0750-8
|View full text |Cite
|
Sign up to set email alerts
|

Glycemic control by the SGLT2 inhibitor empagliflozin decreases aortic stiffness, renal resistivity index and kidney injury

Abstract: BackgroundArterial stiffness is emerging as an independent risk factor for the development of chronic kidney disease. The sodium glucose co-transporter 2 (SGLT2) inhibitors, which lower serum glucose by inhibiting SGLT2-mediated glucose reabsorption in renal proximal tubules, have shown promise in reducing arterial stiffness and the risk of cardiovascular and kidney disease in individuals with type 2 diabetes mellitus. Since hyperglycemia contributes to arterial stiffness, we hypothesized that the SGLT2 inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
106
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 136 publications
(117 citation statements)
references
References 68 publications
8
106
2
1
Order By: Relevance
“…14 In clinical trials, the use of SGLT2 inhibitors has been shown to reduce the quantity of epicardial adipose tissue (independently of effect on body weight), [35][36][37] and these drugs ameliorate the inflammation of adipose tissue surrounding the heart and great vessels 38,39 and the associated abnormalities of cardiac filling and aortic distensibility in both experimental and clinical HFpEF. 18,[40][41][42] Furthermore, SGLT2 inhibitors act to inhibit sodium reabsorption in the proximal renal tubules, in which the majority of renal sodium retention occurs [43][44][45] ; this action explains the marked reduction in plasma and/or interstitial volume and haemoconcentration seen in randomized controlled trials in type 2 diabetes. 25,46 Moreover, SGLT2 inhibitors can attenuate renal inflammation and fibrosis.…”
Section: Sample Size Calculations and Study Conductmentioning
confidence: 99%
“…14 In clinical trials, the use of SGLT2 inhibitors has been shown to reduce the quantity of epicardial adipose tissue (independently of effect on body weight), [35][36][37] and these drugs ameliorate the inflammation of adipose tissue surrounding the heart and great vessels 38,39 and the associated abnormalities of cardiac filling and aortic distensibility in both experimental and clinical HFpEF. 18,[40][41][42] Furthermore, SGLT2 inhibitors act to inhibit sodium reabsorption in the proximal renal tubules, in which the majority of renal sodium retention occurs [43][44][45] ; this action explains the marked reduction in plasma and/or interstitial volume and haemoconcentration seen in randomized controlled trials in type 2 diabetes. 25,46 Moreover, SGLT2 inhibitors can attenuate renal inflammation and fibrosis.…”
Section: Sample Size Calculations and Study Conductmentioning
confidence: 99%
“…149 Empagliflozin, a potent and highly selective SGLT-2 inhibitor, 150 was shown to reduce blood pressure and improve measures of arterial stiffness in diabetic patients. 151,152 However, the protective cardiovascular effect of SGLT-2 inhibitors has been shadowed by the results from postmarketing studies which indicate significant adverse effects, such as an increased risk of diabetic ketoacidosis and leg amputations. 153…”
Section: Uricosuric Medicationmentioning
confidence: 99%
“…Moreover, empagliflozin reduced the levels of CD36 and cardiotoxic lipids improving autophagy in the hearts of ZDF rats [28], and decreased aortic stiffness, renal resistivity index and kidney injury in T2D female mice [29]. Finally, empagliflozin ameliorated kidney injury in T2D female mice by promoting glycosuria, and possibly by reducing systemic and renal artery stiffness [29]. In addition, a redox-sensitive up-regulation of SGLT1 and 2 has been observed in coronary artery ECs in response to high glucose and H 2 O 2 leading to enhanced glucose uptake and induction of atherothrombotic responses [30].…”
mentioning
confidence: 93%
“…Empagliflozin also significantly reduced left ventricle (LV) mass and LV systolic dilatation [25], decreased glucotoxicity thereby preventing the development of endothelial dysfunction, and reduced oxidative stress, cardiac fibrosis and exhibited anti-inflammatory effects in ZDF rats and mice [26,27]. Moreover, empagliflozin reduced the levels of CD36 and cardiotoxic lipids improving autophagy in the hearts of ZDF rats [28], and decreased aortic stiffness, renal resistivity index and kidney injury in T2D female mice [29]. Finally, empagliflozin ameliorated kidney injury in T2D female mice by promoting glycosuria, and possibly by reducing systemic and renal artery stiffness [29].…”
mentioning
confidence: 96%